Analisis Dan Peramalan Daya Dukung Lahan Tanaman Pangan Di Kecamatan Temon Kabupaten Kulon Progo - Dini Hardina; Aris Slamet Widodo; Widodo Widodo (Jurnal Riset Agribisnis dan Peternakan, 2018)
This research aims to determine the carrying capacity of agricultural land food crops in Temon Sub-districts. Data of this research is taken from secondary data obtained from the Central Statistic Agencies and the Department of Agriculture. The data analysis is used to make the levels of the land carrying capacity. Based on the research, the level of the carrying capacity in Temon Sub-district for 10 years in class I. Land carrying capacity value for 10 years in the Temon Sub-district amounted to 2,730. This means that the Temon Sub-district has been able to perform the self-sufficiency. The base of the forecasting in 2017-2020, it shows that Land carrying capacity in Temon Sub-district will decrease every year. In 2020, The land carrying capacity of the Temon Sub-district has predicted in class II. It means that in 2020, Temon Sub-district has been able to do self-sufficiency land food crops but has not been able to provide a decent life for the people. Therefore, the Temon Sub-district should improve land crops and productivity of rice and reduce the rate of populating growth.